Letter (copy) : Assistance for Spain - Tewson, Vincent
032-0065-001 Secretary's. HVT/FC/EK/1025. 19th April, 1939. Mr. W. Elger, Scottish Trades Union Congress, 33, Elmbank Crescent, GLASGOW, C.2. Dear Mr. Elger, ASSISTANCE FOR SPAIN. Many thanks for your letter of the 18th instant enclosing copy of a letter which you have addressed to the Secretary of the Co-operative Wholesale Society. In regard to the P.S. of the letter to Mr. Leckie, the reason I suggested the sending of rolls of material was that if the implements could also be provided (I forgot to mention scissors) the making-up provides employment for the refugees which is a very important factor as it is demoralizing to have no occupation or immediate interests. I have received an intimation this morning that the question of footwear is also important. Probably this is a matter which you might also raise although, of course, it is a very expensive item. If a few cheap sandals could be included it might be helpful. I hear that many of the refugees are using any old pieces of sacking to wrap round their feet. Yours sincerely, Assistant Secretary. 292/946/32/65